The relevance of fiscal rules for fiscal and sovereign yield developments - Afonso, António (2022)
We assess whether numerical fiscal rules impact budget balances and sovereign yields. For a panel of 27 EU countries between 1990 and 2011, we find that fiscal rules reduce budget deficits, specifically expenditure rules, while countries with better fiscal rules experienced lower sovereign bond yields.